Rollover Stability Analysis and Layout Optimization of a Delta E-trike - Fitri Endrasari; Djati Wibowo Djamari; Bentang Arief Budiman; Farid Triawan (Automotive Experiences, 2022)
This study derives a rollover index for a delta E-trike. Past works derive the rollover index by considering lateral centrifugal force only. In contrast, this study proposes a rollover index which is derived under the assumption that the centrifugal force act in both lateral and longitudinal direction. This assumption will give a result closer to the real-life application. In addition, a parametric study on the effect of center of gravity location on rollover index is also proposed. The study continued with the layout assessment, which is done as the considerations in rearranging the powertrain components inside the E-trike. The comparison between initial and new layout shows that the new arrangement gives several advantages to the delta E-trike.